Antimelanogenesis and skin-protective activities of Panax ginseng calyx ethanol extract - Jeong-Ook Lee; Eunji Kim; Ji Hye Kim; Yo Han Hong; Han Gyung Kim; Deok Jeong; Juewon Kim; Su Hwan Kim; Chanwoong Park; Dae Bang Seo; Young-Jin Son; Sang Yun Han; et al. (Journal of Ginseng Research, 2018)
Background: The antioxidant effects of Panax ginseng have been reported in several articles; however, little is known about the antimelanogenesis effect, skin-protective effect, and cellular mechanism of Panax ginseng, especially of P. ginseng calyx. To understand how an ethanol extract of P. ginseng berry calyx (Pg-C-EE) exerts skin-protective effects, we studied its activities in activated melanocytes and reactive oxygen species (ROS)–induced keratinocytes. Methods: To confirm the antimelanogenesis effect of Pg-C-EE, we analyzed melanin synthesis and secretion and messenger RNA and protein expression levels of related genes. Ultraviolet B (UVB) and hydrogen peroxide (H2O2) were used to induce cell damage by ROS generation. To examine whether this damage is inhibited by Pg-C-EE, we performed cell viability assays and gene expression and transcriptional activation analyses. Results: Pg-C-EE inhibited melanin synthesis and secretion by blocking activator protein 1 regulatory enzymes such as p38, extracellular signal-regulated kinases (ERKs), and cyclic adenosine monophosphate response element–binding protein. Pg-C-EE also suppressed ROS generation induced by H2O2 and UVB. Treatment with Pg-C-EE decreased the expression of matrix metalloproteinases, mitogen-activated protein kinases, and hyaluronidases and increased the cell survival rate. Conclusion: These results suggest that Pg-C-EE may have antimelanogenesis properties and skin-protective properties through regulation of activator protein 1 and cyclic adenosine monophosphate response element–binding protein signaling. Pg-C-EE may be used as a skin-improving agent, with moisture retention and whitening effects. Keywords: Antimelanogenesis, Calyx of berry, Matrix metalloproteinases, Panax ginseng, Skin protective